The Photographic Coverage Of Farmers Protest In India 2020: An Aesthetical Perspective Of Published Photographs - Mengi, Nitin Kumar; Sharma, Dr. Trishu (The journal of contemporary issues in business and government, 2021)
The world is very fast especially after the COVID 19 Pandemic take over the charge to rule the daily lives of society all over the world. People spend most of their time during lockdown watching mobile phones , uploading pictures , clicking pictures as smart phone is become one of the most powerful tool to click pictures & upload it on different social platforms instantly. Picture actually speaks more than a text whatever we eat or drink, wherever we go, family selfies, whosoever joins us is all on digital platforms. Even the big Industries of Modern Media, also do’s the same reason is simple, the impact the photographs on society on daily basis. The researcher will study the impact of photographs being published by considering various aspects of aesthetical impact of ongoing farmers protest in India, against the farmers’ bill proposed by the Govt. of India. Researcher used the Comparative analysis of 7 different profiles & publication houses to establish the research to analyze a different perspective in it.